2017
DOI: 10.1177/0269215517698028
|View full text |Cite
|
Sign up to set email alerts
|

Dual task training in persons with Multiple Sclerosis: a feasability randomized controlled trial

Abstract: The study procedures were found to be feasible and improvements should be made in recruitment efforts going forward. Further examination of dual task training programs in individuals with multiple sclerosis is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 27 publications
4
14
1
Order By: Relevance
“…Both, the DTT and the SMT, intervention groups showed improvements in dual task walking as shown by increased absolute dual task gait speed during the dual 'walk'-conditions. This is consistent with earlier studies on DTT in MS, reporting similar findings between training-groups on absolute dual task gait speed while subtracting or alternating the alphabet, supporting the task automatization hypothesis [16,17].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both, the DTT and the SMT, intervention groups showed improvements in dual task walking as shown by increased absolute dual task gait speed during the dual 'walk'-conditions. This is consistent with earlier studies on DTT in MS, reporting similar findings between training-groups on absolute dual task gait speed while subtracting or alternating the alphabet, supporting the task automatization hypothesis [16,17].…”
Section: Discussionsupporting
confidence: 92%
“…Only two studies on DTT compared to single task training have been conducted in pwMS. Sosnoff et al reported a trend for greater gait speed under dual task conditions after a DTT compared to a single task training [16], while Monjezi et al reported similar improvements in dual task walking after both types of training [17]. However, neither study examined the effects on the DTC and the Sosnoff et al study was a feasibility study with a small sample size and no follow-up.…”
Section: Introductionmentioning
confidence: 98%
“…Overall, there is promising evidence for aerobic and resistance exercise improving walking performance, and preliminary evidence supporting aerobic exercise for improving cognitive performance in MS ( Dalgas et al, 2008 ). However, cognitive therapies are not yet being used for potentially improving motor disability, although cognitive-motor interactions powerfully activate motor performance ( Sosnoff et al, 2017 ), possibly reducing total time needed for treatment, and cost of care. For instance, Sosnoff et al (2017) reported that a dual task training program, incorporating cognitive tasks in balance and walking training, improved gait speed and visuospatial memory in a sample of MS patients compared to a single task training program focused on balance and walking function only.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it suggested that when performing a dual-task that required visual attention, the poor postural control observed in older adults was the result of the visual information being assigned to the task and the vestibular information dominating the postural regulation. Dual-tasking has been employed as a balance training program to improve mobility performance in older adults [33], or other neurologically-impaired persons [34]. This redistribution of postural regulations could provide insights for further development of dual-task to train specific postural regulation strategies accordingly.…”
Section: Discussionmentioning
confidence: 99%